Frequency and Risk Factors for Retinopathy of Prematurity in Very Low Birth Weight Infants in NICU, BSMMU (TAJ: Journal of Teachers Association, 2019)
Introduction: Retinopathy of prematurity (ROP) is emerging as an important avoidable cause of childhood blindness both in developed and developing countries that primarily affects premature and very low birth weight infants. There has been paucity of studies on this topic in Bangladesh and there is no national prevalence data on ROP to understand the real burden of the disease. Hence this study has been undertaken to see its frequency and risk factors for ROP in very low weight infants admitted in NICU, BSMMU.Objectives: To find out the frequency and risk factors for ROP in very low birth weight infants admitted in NICU, BSMMU.Methodology: It was a prospective observational study and was carried out in the Department of Neonatology and Department of Ophthalmology, BSMMU from January 2014 to June 2015. Considering all inclusion and exclusion criteria total 162 very low birth weight neonates were enrolled in the study. ROP screening was performed as per unit protocol. All eye examinations were undertaken by experienced ophthalmologist who was especially trained in ROP.Result: Out of 162 study population, one hundred forty fore (88.9%) were very low birth weight, 18(11.1%) were extremely low birth weight and mean birth weight was 1294.35 (SD: 180.96) g. Frequency of ROP was 38(23.5%), where 30(20.83%) among very low birth weight (VLBW) and 8(44.44%) were among ELBW neonates. Out of 38 ROP cases, 5(13%) had stage 1 retinopathy, 3(8%) had stage 2 retinopathy, 16(42.1%) had stage 3 and remaining 14(36.8%) neonates had APROP. On univariate analysis seventeen factors were found to be significant but on stepwise logistic regression analysis only lower gestational age [OR=5.014; CI(95%),2.160-11.640, P=.001] and use of mechanical ventilator [OR=1.925; CI(95%),1.133-3.269, P=.015] was found to be the most significant for causation of ROP.Conclusion: The overall frequency of ROP was 38(23.5%), where as 30(20.83%) were among VLBW and 8(44.44%) were among ELBW neonates. Prevention of prematurity and judicious use of ventilator may reduce the incidence and severity of ROPTAJ 2019; 32(1): 54-61